Short Communication: Pattern of antibiotic resistance on extended-spectrum beta-lactamases genes producing Escherichia coli on laying hens in Blitar, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wibisono FJ, Sumiarto B, Untari T, Effendi MH, Permatasari DA, Witaningrum AM. 2020. Short Communication: Pattern of antibiotic resistance on extended-spectrum beta-lactamases genes producing Escherichia coli on laying hens in Blitar, Indonesia. Biodiversitas 21: 4631-4635. The aims of this study were to determine the susceptibility pattern of phenotypic antibiotics on extended-spectrum beta-lactamases (ESBL) genes and genotype profiles of ESBL producing Escherichia coli strains isolated from cloacal samples of laying hens in Blitar. A total of 165 cloacal swab samples were successfully isolated 145 E. coli strains during the study taken from 5 subdistricts in Blitar. All the strains were examined for antibiotic resistance patterns by disk diffusion method with double-disk synergy test (DDST), followed testing with VITEK® 2 methods, molecular identification of ESBL coding genes using PCR. The results of this study showed that the characterization of nucleotide analysis from PCR amplification of ESBL-producing E. coli bacteria isolated from laying hens in Blitar showed that eight isolates were the dominant of CTX gene, followed by the TEM encoding gene of two isolates, and the SHV coding gene as much as one isolate. The presence of more than 1 encoding genes in the E. coli bacterial isolate was seen in 1 isolate, where the isolate carried the CTX gene and the SHV gene as well. All ESBL producing E. coli isolates were resistant to amoxicillin, ampicillin, cefazolin, cefotaxime, and ceftriaxone, and these ESBL isolates were more than 70% resistant to gentamicin, aztreonam, and trimethoprim/sulfamethoxazole. These results indicated that poultry is a potential reservoir for ESBL-producing E. coli. The presence of ESBL-producing E. coli in poultry requires strengthening antibiotic policy. This is important because the regulation of antibiotic use in poultry is gaining momentum to increase animal productivity and food safety in Blitar, Indonesia.
Keywords: antimicrobial resistance; ESBL genes; Escherichia coli; food safety